2018
DOI: 10.15252/embj.201798714
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the nuclear import of histones H3.1 and H4 as monomers

Abstract: Newly synthesised histones are thought to dimerise in the cytosol and undergo nuclear import in complex with histone chaperones. Here, we provide evidence that human H3.1 and H4 are imported into the nucleus as monomers. Using a tether‐and‐release system to study the import dynamics of newly synthesised histones, we find that cytosolic H3.1 and H4 can be maintained as stable monomeric units. Cytosolically tethered histones are bound to importin‐alpha proteins (predominantly IPO4), but not to histone‐specific c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
76
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(91 citation statements)
references
References 93 publications
15
76
0
Order By: Relevance
“…However, the EX1 kinetics detected in our study for monomeric histones are extensive and expand the entire protein sequence (omitting the N-terminal tails), suggesting high conformational flexibility, in contrast to histones engaged in complexes where EX1 behavior is confined to short regions. Considering recent evidence showing that H3 and H4 monomers associate with importin-beta proteins and are imported into the nucleus in a monomeric state expands their interaction network further (70). We presume that a high degree of flexibility is a feature of histones required to counterbalance the breadth of chaperones that regulate their nuclear import and assembly into nucleosomes and provide exciting directions for future studies.…”
Section: Fig 3 Peptide Maps Following Digestion With Cathepsin-l Omentioning
confidence: 89%
See 1 more Smart Citation
“…However, the EX1 kinetics detected in our study for monomeric histones are extensive and expand the entire protein sequence (omitting the N-terminal tails), suggesting high conformational flexibility, in contrast to histones engaged in complexes where EX1 behavior is confined to short regions. Considering recent evidence showing that H3 and H4 monomers associate with importin-beta proteins and are imported into the nucleus in a monomeric state expands their interaction network further (70). We presume that a high degree of flexibility is a feature of histones required to counterbalance the breadth of chaperones that regulate their nuclear import and assembly into nucleosomes and provide exciting directions for future studies.…”
Section: Fig 3 Peptide Maps Following Digestion With Cathepsin-l Omentioning
confidence: 89%
“…Most histone chaperones have a preference for binding and importing histone heterodimers (69), and HX structural information has been focused mainly on the analysis of heterodimers (34), tetramers (29) and nucleosomes (30,31) or on heterodimer-chaperone interactions (32)(33)(34)(35)(36), disregarding monomeric states. Recent evidence, however, has shown that H3 and H4 are predominantly monomeric in the cytosol and can be rapidly imported into the nucleus bound tightly to importin-␤ proteins (70). Obtaining structural information at the monomer level, therefore, is crucial for delineating structural elements governing histone-chaperone interactions.…”
Section: Fig 2 Specificity Of Cathepsin-l Derived From Histone Digementioning
confidence: 99%
“…Such NLSs, even if they are present in prokaryotic proteins, can interact with karyopherins. Karyopherins have many functions in the cell and, in particular, can act as chaperones [26,27]. The protein domains interacting with karyopherins might have evolved before the origin of the nuclear envelope, with these domains containing sequences that potentially play a role in NLSs.…”
Section: Discussionmentioning
confidence: 99%
“…Karyopherins have many functions in the cell and, in particular, can act as chaperones [26,27]. The protein domains interacting with karyopherins might have evolved before the origin of the nuclear envelope, and these domains contained sequences that can potentially play a role in NLSs.…”
Section: Discussionmentioning
confidence: 99%